Penerapan Model Pembelajaran Inkuiri Terbimbing Berbantuan Mind Mapping pada Mata Pelajaran Fisika SMK Kelas X - Sunni, M. Abdurrahman; Islami, Anggun Variasi (Lembaga Yasin AlSys, 2023)
This study aims to determine the effect of the mind mapping-assisted guided inquiry learning model on physics learning outcomes in class X students of SMK Al Amin Kilang. This type of research is a quasi-experimental study with a pretest-posttest control group design. The population of this study was all students of class X SMK Al Amin Kilang, and the samples selected were class X TKJ A as the experimental class and class X TKJ B as the control class. The sample was selected using cluster random sampling techniques. Data collection was carried out through the results of students' physics learning on magnetism material. Data analysis techniques were carried out using a two-party t test. From the analysis of the two-party t-test data, it was obtained that t count > t table at a significant level of 5%, namely t count = 2.341 > t table = 2.000. From the results of the study, it was found that the average value of the experimental class using the guided inquiry model assisted by mind mapping was higher when compared to the control class using the conventional learning model (lecture). These results indicate that the use of the mind mapping-assisted guided inquiry learning model has a positive effect on the physics learning outcomes of class X students at SMK Al Amin Kilang in the 2022-2023 Academic year.